Chitosan/nanocellulose electrospun fibers with enhanced antibacterial and antifungal activity for wound dressing applications - Ribeiro, Ana S. (2021)
The combination of biodegradable fibers at nanoscale with plant-based extracts is attracting increasing attention to produce wound dressing systems. In this work, nanofibers based on chitosan (CS), poly(ethylene oxide) (PEO), cellulose nanocrystals (CNC) and acacia plant-based extract were developed by electrospinning. Firstly, the polymeric formulations and electrospinning parameters were optimized, resulting in nanofibers with average diameters of 80 nm. CNC were successfully introduced into the optimized CS/PEO blend and the membranes were characterized by FESEM, ATR-FTIR, TGA, XRD, WVTR and WCA. The CNC incorporation improved the nanofibers' physical integrity, morphology, diameters, water vapor transmission rate and thermal properties. After acacia introduction into the best CS/PEO/CNC system, the antibacterial effect was relatively maintained while the antifungal activity was enhanced for some fungi, demonstrating its great effect against a wide range of microorganisms, which is crucial to prevent or treat infections. All the developed systems exhibited absence of cytotoxicity in non-tumor cells, suggesting their biocompatibility. Finally, a continuous release of the acacia extract was observed for 24 h, showing its prolonged action, which contributes to the healing process while reduces the frequency of dressing's replacement. Overall, the developed nanofibers are very promising to act as localized drug delivery systems for wound care applications.